Baures, tierra del chocolate... (CEFREC : CAIB, 2007)
The Baure indigenous people, since ancient times, have owned large areas of chocolate from which they sought out the coveted product. In the "serra del chocolate," as they call it, they exploited this natural resource for the benefit of their communities, until the businessmen seized their lands. Today the Baure people, located in the province of Iténez of the Department of Beni, have been left with very little extension of these lands. They claim that the fight has not stopped and they will continue to defend their ancestral lands at any cost. --